ASPECTS REGARDING THE IMPORTANCE OF TECHNICALTACTICAL EXERCISES DEPENDING ON THE SPECIFICS OF THE POSITION - QUARTERBACKS / DEFENDERS - Cătălin-Andrei Tatarcan (Annals of the “Ştefan cel Mare” University: Physical Education and Sport Section - The Science and Art of Movement, 2020)
Following the application of technical-tactical exercises specific to the defense players (quarterbacks) listed below, I noticed an improvement in terms of technique specific to the position. They improve their 1 to 1 game around the opponent, placement on the field, aerial duels, hitting the ball with both foot and head. The study was conducted on a group of children from the Luceafărul Bucovina Suceava Club.